Correlating acetabular lateral inclination and anteversion using post operative AP-view pelvic x-rays with clinical outcome in cemented total hip arthroplasties - Panicker, Govind Kishen (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Cemented total hip arthroplasty (THA) is one of the most highly successful procedures in the orthopaedic field and further improvements in terms of component materials and bearing surfaces to provide low friction, has increased implant longevity even further. Dislocation is the most devastating complication that can arise from total hip arthroplasty and a malpositioned acetabular cup is the main determinant. Although there are patient and technical factors, acetabular orientation still remains under the direct control of the operating surgeon. Numerous studies have placed an importance on acetabular component positioning termed the “safe zone” based on dislocation rates. However, there is a lack of literature demonstrating the effect of acetabular component positioning on clinical outcome scores. A total of 64 patients underwent THA from January 2008 to December 2011, of which only 60 were included in this study. They comprised of 61.7% were females and 38.3% males. Mean age of respondents based on this study, was 59.03 years for females and 61.04 years for males. Post-operative anteversion and lateral inclination angles were measured and calculated from post-operative x-rays taken at 1 month, 3 years and 5 years. Harris hip score grading was done on the 5th year of follow up. 5 years post-operative clinical outcome using Harris Hip Score showed excellent results in 71.7% of the study group, while 21.7% scored good results and fair result was obtained in only 6.7%. 2 cases encountered some late complications in the form of aseptic loosening, which accounts for a 3.3% complication rate. Analysing the ANOVA and correlation (Pearson) test, Harris hip score showed significant positive correlations with age as well as lateral inclination angles measured at 3rd and 5th year post op with P values of 0.005, 0.016 and 0.019 respectively. Mean anteversion angles of 17.03° and 17.42° and mean lateral inclination of 41.74° and 42.69° after 5 years of THA also produces similar excellent and good clinical outcome scores respectively. The 5 year post-operative clinical outcome score was excellent in general, as the mean Harris hip score was 90.38. There is a weak correlation between radiologic findings of lateral inclination angle with clinical outcome grading. This study shows that although there is a correlation between lateral inclinations with clinical outcome, the correlation is weak and therefore, surgeons may have more manoeuvrability in placing the acetabular component than previously believed.